DETERMINATION OF RADON AND URANIUM CONCENTRATION IN THE PETROLEUM PRODUCTS AT THE ALQAYARA AND ALKASIK NINEVAH GOVERNATE REFINERIES - RAND O. Farqad; Rasheed M. Yousuf; Nabhan A. Hamdoon (Scholar Express Journal, 2022)
Determination of radon gas (Rn222), uranium (U238) concentrations, and the effective activity of (ARn222) in crude oil and petroleum products (asphalt sial, solid asphalt, heavy gas oil, light gas oil, kerosene, naphtha, RCR (Ramsbottom carbon residual ), diesel, light naphtha, and fuel oil) using CR-39 detector at the Al-qayara and Al-kasik refineries. It was found that the radon gas concentration in crude oil (8.418 Bq/m3) and petroleum products ranged from (9.329 Bq/m3) to (1.663 Bq/m3) with an average value of (5.496 Bq/m3) at Al-qayara refinery, the higher and lower values of radon gas effective activity in the samples of products of Al-qayara refinery (10.728 ± 2.469 Bq/kg) with an average of (6.598 Bq / kg), while for Al-kasik refinery was the radon gas concentration in crude oil is (10.937 Bq/m3) and in petroleum products ranged from (8.581 Bq/m3) to (1.931 Bq/m3) with an average of (5.256 Bq/m3). As for the concentration limits of Uranium-238 from (0.928 ppm) to (0.232 ppm) with an average value of (0.58 ppm) at Al-qayara refinery, and from (0.862 ppm) to (0.206 ppm) with an average value of (0.534 ppm) at the Al-kasik refinery site. The higher and lower values of the radioactivity of radon gas at the Al-kasik refinery samples (12.07 ± 2.91 Bq/kg) with an average of (7.49 Bq/kg). By comparison, we found all results in the limitations of ICRP regulations.
Keywords: Radon; Uranium; CR-39 detector; petroleum products